2004
DOI: 10.1088/0022-3727/38/1/024
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the effects of the dose rate and temperature on zircon thermoluminescence

Abstract: After exposure to ionizing irradiation, mineral zircon exhibits thermoluminescence (TL), which can be used to calculate the irradiation dose and the age of natural samples. Different aspects of the dating procedure based on zircon TL, including laboratory added irradiation at room and elevated temperatures, fading and preheat processes, have been considered within the framework of the kinetic model developed by our group earlier. It is shown that dose rate effects arising due to the difference between natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A comprehensive consideration of the scenarios associated with the dating methodology, based on the zircon TL, will be published elsewhere 4 [21].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive consideration of the scenarios associated with the dating methodology, based on the zircon TL, will be published elsewhere 4 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown (e.g. Turkin et al, 2005) that zircon exhibits OSL and TL glow peaks located between 50 C and 200 C due to recombination of trapped holes and electrons released from shallow traps. Zircon is the main transparent heavy mineral in our samples and these peaks might eventually affect the results of the OSL and TL sensitivities of bulk samples.…”
Section: Methodsmentioning
confidence: 99%
“…The oxygen vacancies can be considered as the origin of the very common 340 nm band in silicates describing the process as a result of Si-O bond breakings during mechanical or thermal stress in the silicate lattices (Garcia-Guinea et al, 2007a, b). The band at 400 nm can be due to [AlO 4 /M + ] 0 centers; the sharp emission at 480 and 580 nm can be, respectively, linked to Dy 3+ impurities in Zr holes (Turkin et al, 2005); the bands peaked at 560 and 750 nm could be assigned to Mn 2+ point defects and Fe 3+ centers (Telfer and Walker, 1975). Finally, the 980 nm sharp waveband could be explained due to Yb 3+ centers (Gorobets and Rogojine, 2002).…”
Section: Luminescence Responsementioning
confidence: 99%